The relation between capital ratios and banks’ financial performance - Pedroso, Afonso Amaral Penaforte (2021)
This dissertation seeks to answer a question on which there is a vast literature but not much consensus: the relation between the capital ratios and banks’ financial performance. This questions is revisited resorting to a two-steps analysis, by firstly estimating the linear correlation on all the performance and capital parameters as dependent and independent variables respectively, followed by a multiple regression analysis, employing only a set of the variables analysed in the correlation analysis. This analysis led to the conclusion that capital ratios hold a negative relationship with banks’ financial performance. Moreover, this dissertation has also found that when employing net income over assets or return on assets the results are consistent, independently on which variable is adopted as dependent variable. On the contrary, the conclusions are quite different when analysing the Total Capital to risk-weighted assets ratio or the Total Capital to total assets ratio.